A MODEL HOW TO CREATE SOCIAL VALUE ADDED FOR COMPANY IN INDONESIA - Maharani Rahma (Dinasti Publisher, 2020)
The purpose of establishing a company can be divided into two, economic goals and social goals. Economic goals regarding the company's efforts to maintain it’s existence, the company's social goals are expected to meet the desires of investors, employees, providers of factors of production and the wider community. Both of these goals support one another, the company will not be able to realize its social goals if the company has not been able to achieve the company's economic goals. Social Value Added (SVA) which is an adaptation of Economic Value Added (EVA) is one of the tools to assess a company's performance to achieve social goals. The positive SVA shows that the social influence created by the company has yielded results in excess of the capital costs that must be incurred, which will later be proven by obtaining